Degradation of multidrug-resistant E. coli by low pressure plasma. Issue 1 (1st January 2021) - Ahmed, Muhammad Waqar; Naqvi, Syeda Masooma; Qasim, Irfan; Noreen, Zobia; Shafiq, Muhammad; Bukhari, Habib
ABSTRACT: Owing to its nontoxicity and better efficiency, low-temperature plasma (LTP) has been proposed to be a strong antibacterial agent against multidrug-resistant bactericidal pathogens. On the other hand, previously several food-borne pathogens were treated by chemically hazardous and least-efficient irradiation techniques. Because of its superior efficiency, in the current study, we implemented LTP protective mechanism against Escherichia coli (E.coli) . In particular, we investigated the sterilization effects of plasma on the degradation of pure samples of E.coli strain ( 10 7 colony forming units) in the presence and absence of H 2 O 2 fumes. Interestingly, the proposed mechanism improved considerably the microbial reduction, inactivation efficiency and kill rate of the plasma-treated E.coli samples. The decrease in bactericidal cell viability was confirmed by deoxyribonucleic acid (DNA) quantification and membrane damage by protein leakage test. The reactive oxidants species (ROS) were explored via optical emission spectroscopy (OES). For the investigation of the surface characteristics, we carried out the scanning electron microscopy (SEM) analysis of the plasma-treated nutrient media containing E.coli colonies. The reported results confirmed that low pressure and low temperature plasma can be a potential alternative for the degradation of multidrug-resistant E. coli .